SIRT7 is a histone desuccinylase that functionally links to chromatin compaction and genome stability - Lei Li (Nature Portfolio, 2016)
SIRT7 is a member of sirtuin family proteins that are described as NAD+-dependent class III histone deacetylases. Here, the authors show that SIRT7 is histone desuccinylase catalysing H3K122 desuccinylation, thereby promoting chromatin condensation and repair of DNA double strand breaks.